Female labour force participation in Perak Darul Ridzuan, Malaysia: a demographic empirical analysis with survey data / Thavamalar Ganapathy and Prof. Dr. Madya Norasibah Abdul Jalil - Ganapathy, Thavamalar; Abdul Jalil, Norasibah (Universiti Teknologi MARA, Cawangan Melaka, 2022)
The purpose of this study is to investigate the demographic determinants of women's employment in Perak Darul Ridzuan. The data is collected through the survey via distribution of questionnaire. A Binary Regression Model is used to estimate the effects of the determinants of female labour force participation in Perak, Malaysia. Based on the results from the binary regression model, age and race are among the factors that significant at one percent, field of study and education status significant at five percent and marital status significant at ten percent which affects the female employability. The finding from this study is expected to contribute to improving women standard of living as well as their economic status.